Effects of cattle slurry and cultivation on air exchange in sandy and silty soils from northern Norway - HARALDSEN, T.K. (Agricultural and Food Science, 1999)
Gas diffusivity and permeability, and air-filled porosity, were measured in undisturbed soil cores at four water potentials between -1.5 kPa and -60 kPa. Virgin (never ploughed) and cultivated sandy and silty soils from two sites in northern Norway were used in the investigation. The cultivated soils had lower air-filled porosity and gas diffusivity than the virgin ones. Application of slurry (50 Mg ha-1) decreased gas diffusivity and changed the relationship between relative diffusivity and air-filled porosity for both the virgin and cultivated sandy soils and the virgin silty soil. The gas permeability of both the virgin and cultivated silty soil was low, and the relative diffusivity at field capacity less than the limit below which plant growth is affected. Tutkimuksessa verrattiin viljelemättömän (ei koskaan kynnetty) ja viljellyn hiekka- ja hiesumaan huokoisuutta, diffuusionopeutta kaasuille ja ilmanläpäisykykyä. Maanäytteet kerättiin kahdelta paikkakunnalta Pohjois-Norjasta. Näytteistä, joissa maan luontainen rakenne oli säilytetty, määritettiin kaasun diffuusiokerroin ja ilmanläpäisykyky sekä ilman täyttämä huokostila neljässä eri veden potentiaalissa, joka vaihteli välillä -1,5 kPa ja -60 kPa. Viljeltyjen maiden ilman täyttämä huokostila ja kaasun diffuusiokyky olivat pienempiä kuin viljelemättömien. Lietelannan levitys (50 Mg ha-1) vähensi kaasun diffuusiokykyä ja muutti suhteellisen diffuusionriippuvuutta ilman täyttämästä huokostilasta sekä viljelemättömällä että viljellyllä hiekkamaalla ja viljelemättömällä hiesumaalla. Kaasunläpäisykyky sekä viljelemättömällä että viljellyllä hiesumaalla oli pieni ja suhteellinen diffuusiokyky jäi maan kosteuden vastatessa kenttäkapasiteettia pienemmäksi kuin raja, jonka alapuolella kaasun vaihto rajoittaa kasvin kehitystä.